Romania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix provides an estimate of the long-term path of Romania's real exchange rate. The paper describes the recent history of the real exchange rate and its main determinants. A model is developed of a time-varying long-term exchange rate path, mainly driven by the terms of trade and net foreign direct investment. This long-term path is then used to assess the developments in Romania's actual exchange rate. The paper also examines Romania's growth potential in the medium term.